"We Are a Service, Not an Authority": Multiple Institutional Logics in a Swiss Youth Welfare Office. An Ethnographic Case Study From Street-Level Bureaucracy - Koch, Martina; Piñeiro, Esteban; Pasche, Nathalie (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2019)
In 2013, Switzerland enacted a new law regarding child and adult protection. As a result, the Swiss child welfare system underwent legal, organizational, and structural changes. Due to the new law, the cantons and municipalities had to reorganize their responsibilities in the area of child and adult protection and and set up so-called Child and Adult Protection Agencies. In this process, new professional and organizational roles and self-conceptions emerged which generated ambivalences and contradictions that are partially symptomatic of "street-level bureaucracy" (LIPSKY, 1980). Based on an ethnographic case study, in this article we explore how the youth welfare office we examined deals with requirements emerging from multiple institutional logics. Applying the concept of "institutional logics" (THORNTON & OCASIO, 2008) we draw on considerations from new institutionalism. Ambivalent or even conflicting logics in the youth welfare office examined not only are shown to be entangled but their indistinguishability opens up organizational room for maneuver. These results may be partially generalized to other street-level bureaucracies.